Makna Teologis dan Nilai Antropologis Tradisi Natoni dalam Kehidupan Masyarakat Kristen - Veren Veronika Manu; Yohana Angelina Pobas; Yusmin Tapeun; Jello Ottu; Yenry Anastasia Pellondou (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2026)
The Natoni tradition, as an oral cultural heritage of the Timorese community, embodies religious and social dimensions that reflect the relationship between Christian faith and local wisdom. However, the currents of modernization and shifts in the lifestyle of younger generations have led to a diminishing understanding of its symbols, ritual language, and moral messages, thereby placing its existence at risk of marginalization. This study addresses the question of how the theological meaning and anthropological values of Natoni are understood and actualized within Christian communities, and to what extent this tradition contributes to the formation of faith identity and social cohesion. A descriptive qualitative approach was employed, utilizing in-depth interviews, participatory observation, and document analysis to obtain a comprehensive understanding of the practice and its meanings. The findings reveal that Natoni functions as a contextual medium of prayer, a means of internalizing faith teachings, a bond of communal solidarity, and a vehicle for transmitting values of respect, responsibility, and intergenerational togetherness. The tradition provides an integrative space between incarnational theology and local cultural realities, thereby enriching contextual expressions of Christian spirituality. The study concludes that the revitalization of Natoni requires synergy among the church, traditional leaders, families, and educational institutions to ensure its continued relevance and responsiveness to contemporary challenges. The novelty of this research lies in its simultaneous integration of theological and anthropological analyses of Natoni as a contextual praxis of faith rather than merely a cultural phenomenon, thus offering a conceptual contribution to the development of Indonesian contextual theology.